The Evaluation of Arabic Textbook for the Class V in the perspective of Rushdi Ahmad Tuaimah - Halomoan Halomoan (Universitas Negeri Padang, 2025)
A good textbook is very important in the learning process because learning will not be successful without a good book. This research aims to know the criteria that must be identified when writing the Arabic textbook Class V from the perspective of Rushdi Ahmed Tuaimah in one of the Islamic primary schools, namely Bintang Cendekia in Pekanbaru, Indonesia, and to know the validity of its use. The data collection method is the interview and the document, and the data analysis method is content analysis and evaluation. Based on the data analysis, the result obtained is that the Arabic textbook scheduled is not good to be used, with it does not yet include some basic and standard of Arabic textbook compilation in terms of language, culture, and education content. It can be generalized that many textbooks are not generated from scientific research and do not consider the principles and criteria in writing a textbook. Therefore, popular textbooks need to be standardized to be good.